Diabetes mellitus and dietary treatment - Krumdieck, Carlos F. (1923)
The causes of diabetes mellitus, are many and varied. I will succinctly in review of all the circumstances that predispose to the onset of the disease, as well as some other disease states, which are sometimes determiantes causes of diabetes.